Evaluación de factores de riesgo ergonómico y su incidencia en la salud de los trabajadores del taller de mantenimiento de motores de combustión interna de una empresa de prestación de servicios petroleros ubicada en lago agrio. Propuesta de un manual de prevención. - Vélez Sánchez, Ramón Vitervo (2017)
The musculoskeletal affections caused by the lack of ergonomic considerations related to work, are one of the most frequent diseases at national and worldwide level. With the aim of improving the working conditions of the workers, CDR-CEE oil services company took the decision to carry out the ergonomic evaluation of the MCI maintenance workshop in a qualitative manner by applying surveys to the study staff, where it was possible to appreciate that the respondents mentioned signs of ergonomic affectation; and quantitatively applying recognized methods the existing ergonomic risks were determined; therefore, a risk assessment matrix was used by the INSHT National Institute of Occupational Safety and Health to determine the level of risk, the NIOSH method to assess the manual lifting of loads, the ergonomic evaluation method REBA for the evaluation of forced postures during their work activity. The data gathered from ergonomic risk assessments indicate that an intervention in work activities is required to make improvements and prevent severe musculoskeletal affections conditions over time.